Epidemiology Study of Human Metapneumovirus in Malaysia among Paediatric Children below 4 years of age, 2012 - Gunasegaran, Vinomarlini; V., Raman; Samuel, Lihan; Ravindran, Thayan; Saat, Zainah (International Science Community Association, India, 2014)
We have done a specific study on the molecular epidemiology of Human Metapneumovirus cases which was found in Malaysia among paediatric children below 48 months of age from January till December 2012. These paediatric cases were isolated from the rest of those entire positive below 48 months of age. The total number of the positive cases below 48 months of age is 53 cases out of the general population of 438 positive cases. We performed phylogenetic analysis on these patients and a seasonal prevalence hMPV incidence was observed in the month of November. A high level of sequence identity was observed in the A2 subgroup and no amino acid substitution was found compared to the strains observed in Malaysia and other countries. The pairwise distance among the strains belonging to the predominant subgroup A2was0.0925 suggesting highly homologous with seasonal epidemics. Keyword: Molecular epidemiology, human metapneumovirus, polymerase chain reaction (PCR), paediatric, phylogenetic analysis.